Diffusion and transmission of carbapenem-resistant Klebsiella pneumoniae in the medical and surgical wards of a university hospital in Milan, Italy - Anna L. Ridolfo; Sara G. Rimoldi; Cristina Pagani; Andrea F. Marino; Anna Piol; Matteo Rimoldi; Pietro Olivieri; Massimo Galli; Lucia Dolcetti; Maria R. Gismondo (Elsevier, 2016)
Summary: Carbapenem-resistant Klebsiella pneumoniae (CRKP) is emerging as a public health problem worldwide. In Italy, a remarkable increase in CRKP cases has been reported since 2010. In this study, CRKP diffusion, distribution and in-hospital transmission trends were evaluated in a university hospital in Milan, Italy, from January 2012 to December 2013. Isolates from 63 newly detected CRKP-positive patients were genotyped, and possible transmission was determined by combining the molecular results with data concerning the patients' admission and in-hospital transfers. Most of the cases (90.4%) were from general medical and surgery wards, and the remaining 9.6% were from the intensive care unit. Fifteen of the 46 hospital-associated cases (32.6%) were attributable to in-hospital transmission. After the introduction of targeted and hospital-wide control measures, the transmission index significantly decreased from 0.65 to 0.13 (p = 0.01). There was also a decrease in the overall nosocomial case incidence, from 0.37 to 0.17 per 1000 person-days (p = 0.07).Our findings indicate that the spread of CRKP in Northern Italy hospitals may go far beyond high-risk settings (i.e., intensive care units) and that strict surveillance should be extended to general areas of care. Keywords: Multidrug-resistant agents, Carbapenem-resistant Klebsiella pneumoniae, Cross-transmission, Infections control measures, Active surveillance, Active screening